Contribuições da ludicidade na aprendizagem da educação infantil na escola quilombola Antonio Fausto da Trindade em Itaboca - ESPÍRITO SANTO, Maria Aparecida Azevedo do (2023)
The present text proposes a discussion about the “Contributions of playfulness in the learning of Early Childhood Education in the quilombola Antonio Fausto da Trindade school, in Itaboca, municipality of Inhangapi -Pa. General objective: Reflect from the authors' point of view, the ludic perspective in the kindergarten modality. The problem is: What is the value that toys, play and games have in the development of learning of Early Childhood Education students at the A. F. da Trindade quilombola school in Itaboca? The methodology used was based on a bibliographical research, with fieldwork, of a qualitative and descriptive nature. The article was built based on the authors: Amaral (2008/2022), Arroyo (2013), Berticelli, I. A.; Telles, A. M. (2017), and laws such as the 1988 Constitution, the LDB, the PCNs, the RCNEI, and others. As a result of the research, it is pointed out that the contribution of playfulness in learning Early Childhood Education in the quilombola school are: it values memory and strengthens the quilombola identity of the Itaboca community, that teaching dialogues with knowledge, values, cultures and awakens not only for children, but also for adults, how important these cultural traditions, ancestry and orality of the quilombola people are and that they should not be forgotten.